PENGARUH PROFITABILITAS DAN SOLVABILITAS TERHADAP HARGA SAHAM PADA PT MUSTIKA RATU TBK PERIODE 2014 - 2023 - Firnanda, Nadia; Andriyani Hapsari (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to determine the effect of profitability and solvency ratios on the stock price of PT Mustika Ratu Tbk for the 2014–2023 period. The background of this research is the fluctuation in stock prices, which reflects the dynamics of the company’s internal financial performance. The profitability variable is measured using Return on Assets (ROA), while the solvency variable is measured using the Debt to Equity Ratio (DER). This research uses a quantitative approach with an associative research type. The data used are secondary data in the form of annual financial statements and year-end closing stock prices obtained from the Indonesia Stock Exchange. The data analysis technique employed is multiple linear regression using IBM SPSS version 27. The results show that partially, ROA has a positive and significant effect on stock price, with a t-value of 7.253 and a significance level of < 0.001. On the other hand, DER does not have a significant effect on stock price. Simultaneously, ROA and DER have a significant effect on stock price, with an F-value of 35.073 and a significance level of 0.001. The coefficient of determination (R²) is 0.909, indicating that 90.9% of the variation in stock price can be explained by ROA and DER, while the remaining 9.1% is influenced by other factors outside the model. These findings suggest that profitability is a key factor affecting stock prices, while DER has no significant impact.